Collaborative Playlists around the World: A Cross-Cultural User Study - So Yeon Park; Jin Ha Lee; Audrey Laplante; Xiao Hu; Blair Kaneshiro (Transactions of the International Society for Music Information Retrieval)
Collaborative playlists (CPs) enable users of streaming platforms to share and discover music through co-curation. Recent studies involving predominantly North American samples have found that CPs are created for a variety of contexts, help users organize and access music, facilitate music discovery, and support social connections. Yet, despite these important benefits, little is known about how CP usage aligns or varies across different cultures. We conducted an exploratory study to better understand the landscape of collaborative music engagement with a focus on Hong Kong, South Korea, Quebec, and the United States. We found that across these cultures, previously established purposes for engaging in CPs apply, yet with different degrees of emphasis. Perceived and expected CP outcomes and broader perspectives on social connection through music also varied by location and CP user type. With these findings we discuss primary similarities and differences across the studied cultures and highlight directions for future investigations to further elucidate how music platforms with CP functionalities—and social capabilities more generally—can better help users achieve their desired goals around music.